2022
DOI: 10.30658/hmc.4.8
|View full text |Cite
|
Sign up to set email alerts
|

I Get by With a Little Help From My Bots: Implications of Machine Agents in the Context of Social Support

Abstract: In this manuscript we discuss the increasing use of machine agents as potential sources of support for humans. Continued examination of the use of machine agents, particularly chatbots (or “bots”) for support is crucial as more supportive interactions occur with these technologies. Building off extant research on supportive communication, this manuscript reviews research that has implications for bots as support providers. At the culmination of the literature review, several propositions regarding how factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…First, the existing literature acknowledges the need for machines to express emotions and sincerity to be effective communicators 105 107 . This is particularly important when machines are attempting to restore or repair relationships with humans after violations 106 , 108 , 109 . Scholars have sought to design robots to display emotions during communications with humans to overcome this issue 110 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the existing literature acknowledges the need for machines to express emotions and sincerity to be effective communicators 105 107 . This is particularly important when machines are attempting to restore or repair relationships with humans after violations 106 , 108 , 109 . Scholars have sought to design robots to display emotions during communications with humans to overcome this issue 110 .…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have sought to design robots to display emotions during communications with humans to overcome this issue 110 . Nonetheless, other scholars have argued that even with added design features machines are still likely to be perceived as being incapable of feeling or thinking 106 , 111 . The results of this study, however, bridge the gap between these two opposing views.…”
Section: Discussionmentioning
confidence: 99%
“…Machines and AI can offer social support to people as well. Interdisciplinary research suggests that people believe interactive machines can provide support in all kinds of situations (Abendschein, Edwards, & Edwards, 2021; Beattie & High, 2022), including education (Dhimolea et al, 2022; Edwards et al, 2022). For example, researchers using robot cats in an academic library found that even brief interactions between students and the robotic animals reduced self‐reported stress levels (Edwards et al, 2022).…”
Section: Study Two: the Influence Of Immediacy And Social Supportmentioning
confidence: 99%
“…The healthcare industry is evolving around innovative methods and emerging technologies, such as conversational agents, to improve the health and wellbeing of the population (Campbell & Jovanovic, 2021;Wang et al, 2022) and support the human social and psychological needs (Beattie & High, 2022). Furthermore, such agents support users during crisis and stressful events by providing information, emotional, and companionship support (Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%